2012
DOI: 10.1163/156854112x631926
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, frequency and occurrence of cereal nematodes on the Central Anatolian Plateau in Turkey and their relationship with soil physicochemical properties

Abstract: Tbe distribution of important plant-parasitic and free-living nematodes in tbe cereal production areas of tbe Central Anatolian Plateau (CAP) of Turkey was investigated witb systematic surveys. Two important plant-parasitic nematode groups were found widely distributed; cereal-cyst nematodes (78.3%) and root-lesion nematodes (42.6%). Cereal cyst nematodes (CCN) were identified as Heterodera filipjevi in 18 provinces. Heterodera latipons was found in only one province. Pratylenchus thornei and P. neglectus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
3
17
4
Order By: Relevance
“…Later on, H. avenae was reported as widely distributed in the Eastern Mediterranean (Gözel 2001;Subbotin et al 2003;Imren et al 2012Imren et al , 2013a as well as in the Thrace and Aegean regions (Mısırlıoglu and Pehlivan 2007). H. filipjevi and H. latipons are present in the CAP region; of these, H. filipjevi is the most dominant and was reported in 87 % of surveyed fields (Rumpenhorst et al 1996;Oztürk et al 1998;Abidou et al 2005;Yavuzaslanoglu et al 2012). Generally, H. latipons and H. avenae occur in mixed populations across most wheat growing areas of the SEA and Eastern Mediterranean regions (Kilic 2011;Kilic et al 2012;Imren et al 2012;Ocal 2012).…”
Section: Species Of Ccnmentioning
confidence: 99%
“…Later on, H. avenae was reported as widely distributed in the Eastern Mediterranean (Gözel 2001;Subbotin et al 2003;Imren et al 2012Imren et al , 2013a as well as in the Thrace and Aegean regions (Mısırlıoglu and Pehlivan 2007). H. filipjevi and H. latipons are present in the CAP region; of these, H. filipjevi is the most dominant and was reported in 87 % of surveyed fields (Rumpenhorst et al 1996;Oztürk et al 1998;Abidou et al 2005;Yavuzaslanoglu et al 2012). Generally, H. latipons and H. avenae occur in mixed populations across most wheat growing areas of the SEA and Eastern Mediterranean regions (Kilic 2011;Kilic et al 2012;Imren et al 2012;Ocal 2012).…”
Section: Species Of Ccnmentioning
confidence: 99%
“…Moran's I, inferred using z-score and p value, determines the presence of spatially significant clusters. If z-score value is greater than 2, it indicates highly significant (p < 0.01) clustering; z < −2 indicates significant dispersed (p < 0.01) and z around 0 indicates random distribution (Yavuzaslanoglu et al, 2012). Spatial relationship was conceptualized using fixed distance band where each feature is analyzed within the context of neighboring features.…”
Section: Point Pattern Analysismentioning
confidence: 99%
“…Presence of significant RWTN infestation hotspot and cold spot in Dumri and adjacent blocks of Gawan, Tisri, and Dhanwar, respectively, might help in future to take management decisions. In another example, point pattern geostatistical approach was employed to identify infestation hotspots of the cereal cyst nematode (Heterodera filipjevi) and root lesion nematode (Pratylenchus neglectus, P. thornei) infesting wheat and barley in Turkey (Yavuzaslanoglu et al, 2012). They also found that population density of these nematodes were positively correlated with electrical conductivity (EC) and percentage sand content of soil.…”
Section: Spatial Pattern Of Rwtn Distributionmentioning
confidence: 99%
“…However, the dominant species varied with the region. Heterodera avenae and H. latipons were found in the south-eastern and eastern Mediterranean region, while H. filipjevi was prevalent in the central Anatolian region (Öztürk et al 1998, Abidou et al 2005, Yavuzaslanoglu et al 2012, Imren et al 2012, Dababat et al 2014. Heterodera avenae, H. filipjevi and H. latipons were found in Syria (Rivoal et al 2003, Abidou et al 2005, Hassan et al 2010.…”
Section: Introductionmentioning
confidence: 99%